2008
DOI: 10.1007/s11852-009-0042-2
|View full text |Cite
|
Sign up to set email alerts
|

Sea-level rise and coastal vulnerability: an assessment of Andhra Pradesh coast, India through remote sensing and GIS

Abstract: The eustatic sea-level rise due to global warming is predicted to be about 18 to 59 cm by the 2100 (IPCC 2007), which necessitates identification and protection of vulnerable sections of coasts. Assessment of vulnerability level of Andhra Pradesh (AP) coast as an example is demonstrated in this study using five physical variables, namely coastal geomorphology, coastal slope, shoreline change, mean spring tide range, and significant wave height. A coastal vulnerability index was prepared by integrating the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(65 citation statements)
references
References 32 publications
1
63
0
1
Order By: Relevance
“…Geomorphology also considers the relative resistance of various geological formations occurring at the shoreline to marine erosion processes. Thus, geomorphology is ranked qualitatively according to the relative strength of the coastal landforms and rocks [22] outcropping along the northern coast of the Peloponnese. The predominant coastal landforms in the study area (ranging from very high to very low vulnerability) identified during the field coastal geomorphological mapping were coarse sandy to gravelly beaches, which developed mainly at the aprons of coastal alluvial cones and fan deltas, and marine cliffs composed of various rock types, such as marls, conglomerates, and limestones (Fig.…”
Section: Geological -Structural Variablesmentioning
confidence: 99%
See 2 more Smart Citations
“…Geomorphology also considers the relative resistance of various geological formations occurring at the shoreline to marine erosion processes. Thus, geomorphology is ranked qualitatively according to the relative strength of the coastal landforms and rocks [22] outcropping along the northern coast of the Peloponnese. The predominant coastal landforms in the study area (ranging from very high to very low vulnerability) identified during the field coastal geomorphological mapping were coarse sandy to gravelly beaches, which developed mainly at the aprons of coastal alluvial cones and fan deltas, and marine cliffs composed of various rock types, such as marls, conglomerates, and limestones (Fig.…”
Section: Geological -Structural Variablesmentioning
confidence: 99%
“…Thus, an index that is based on physical variables, such as coastal landforms, geology, relief, shoreline displacement, relative sea-level change, tide range and wave height, has been used to assess the sensitivity of coasts in the USA, Europe, Brazil, India and Argentina [16,[19][20][21][22]. A similar formula, referred to as a sensitivity index, was used by Shaw et al [23] along the Canadian coast while Catto, in an attempt to study the coastal erosion of the island of Newfoundland, proposed two separate indices: a newly developed Coastal Erosion Index (CEI) for the assessment of the sensitivity to short-term erosion and a Coastal Sensitivity Index for the assessment of longer term coastal erosion and susceptibility to sea-level rise [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a considerable amount of subjectivity involved in the case of categorical classes; however, they can be used as indicators in the case of vulnerability assessment. The quantitative classes have been decided based on the expert judgments, literature information (Rao et al, 2008;Kumar et al, 2010;Kumar and Kunte, 2012) and the spectrum of values of the data set considered specific to the region. All these methodologies of classification depict site-specific relative vulnerability thresholds and thus are appropriate for regions with similar environmental conditions.…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…However, Vittal Hegde and Radhakrishnan Reju (2007) used the sum of the value of each variable divided by the number of variables. Later, Nageswara Rao et al (2008) calculated CVI by taking the summation of the variables considered with the ranks of each multiplied by their corresponding weights on the Andhra Pradesh coast.…”
Section: Coastal Vulnerabilitymentioning
confidence: 99%